(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluation of the inpatient experience of breast cancer patients treated at Department of Internal Medicine 6, K Hospital in 2024. Materials and methods: A cross-sectional descriptive study was conducted on 210 breast cancer inpatients at Department of Internal Medicine 6, K Hospital, using the “Patient Experience Survey During Inpatient Hospitalization” as the data collection tool. Results: The median age of participants was 50 years (range: 23-79). Patients reported a high level of positive experience, with a positive response rate of 92.8%. All participants (100%) confirmed they would return to the hospital if they needed treatment in the future. The positive experience rate during the discharge process was 88.1%. High levels of satisfaction were recorded regarding hygiene and security-related factors, including restrooms (99%), availability of hand sanitizer (100%), and visitor access control (89.5%). However, there were areas of dissatisfaction: 11% of patients reported negative experiences with the waiting time for hospital admission procedures; only 4.8% felt they received adequate explanations upon admission; and 13.3% were dissatisfied with information related to medical service pricing. Infrastructure, security, and utility services also showed limitations, with 26.7% reporting a negative experience. Average waiting times for some procedures were as follows: admission procedures (mean 40.6 ± 10 minutes); initial examination upon ward entry (29 ± 13.6 minutes); and discharge process (122 ± 52 minutes). Conclusion: Most breast cancer patients at Department of Internal Medicine 6, K Hospital reported a positive inpatient experience, particularly during the discharge process, with 100% willing to return for future treatment. However, improvements are still needed in information provision, infrastructure, and support services. The waiting time for certain procedures-especially admission and discharge-remains lengthy. The study results provide a basis for proposing solutions to improve service quality and optimize patient experience.